Changes in the demand for urban transport in the Metropolitan Region of São Paulo: Challenges for the post-pandemic period - Daroncho, Celio; Martinez , Pedro Jose Perez (National Journal of City Management, 2025)
Objective – This study aims to investigate and analyze the changes in urban travel patterns within the São Paulo Metropolitan Region (RMSP) resulting from the Covid-19 pandemic. It seeks to identify the factors that influenced modal choice (public transport, private transport, or remote access) for reaching services and performing daily activities in the pre- and post-pandemic periods. Methodology – The research employed a quantitative method, utilizing a questionnaire administered to a sample of 1,034 students from Fatecs located in the RMSP. Data analysis was conducted using logistic regression (Logit) models, which measured the probability of choosing different transport modes and forms of access (in-person/remote) based on the independent variables of gender, age group, and vehicle ownership. Originality/Relevance – The study addresses a gap by providing recent, specific empirical evidence on behavioral transformations in urban mobility in one of the world’s largest metropolises in a post-pandemic context. Its academic relevance lies in applying logistic modeling to understand not only modal choice but also the decision to travel or not, thereby contributing to the literature on transport demand. Results – The main results indicate a significant migration from public to private transport in the post-pandemic period, driven primarily by vehicle ownership and age group. A marked acceleration in the adoption of remote alternatives for accessing services such as banking and shopping was also verified. Conversely, activities like leisure maintained a strong in-person tendency, albeit with a preference for using private vehicles. Theoretical/Methodological Contributions – The study provides a methodological contribution by applying and detailing logistic regression modeling to analyze mobility decisions in a disaggregated manner, including the choice for "non-transport" (remote activities). Theoretically, the results reinforce and update discrete choice models, demonstrating how socioeconomic variables and crisis contexts structurally impact demand patterns. Social and Environmental Contributions – The study’s conclusions highlight a scenario of potential decline in public transport ridership, with negative social implications for the population dependent on this mode. Environmentally, a shift towards private transport could exacerbate congestion and pollution problems. This work informs the formulation of public policies aimed at reconfiguring and incentivizing collective transport, integrated with more sustainable mobility solutions.